2014
DOI: 10.1108/ijwbr-01-2014-0006
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the negative relation between return and conditional volatility in the wine market

Abstract: Purpose – The purpose of this paper is to examine fine wine’s safe-haven status with respect to US equity movements. Design/methodology/approach – We use a generalized autoregressive conditional heteroscedasticity model and its variant to measure the asymmetric reaction to positive and negative shocks. Findings – Our empirical results show an inverted asymmetric volatility in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…Our empirical results indicated a negative dynamic conditional correlation between fine wine and the UK stock market, suggesting the effectiveness of using fine wine as a hedge. With different methodology, this finding corroborates previous studies showing the significant diversification benefits from adding wine to a portfolio comprising stocks (Bouri, 2014; Fogarty, 2010; Kourtis et al, 2012; Masset and Henderson, 2010; Masset and Weisskopf, 2010). However, during periods of extreme stress, fine wine was a very weak safe haven against the UK stock market risk.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Our empirical results indicated a negative dynamic conditional correlation between fine wine and the UK stock market, suggesting the effectiveness of using fine wine as a hedge. With different methodology, this finding corroborates previous studies showing the significant diversification benefits from adding wine to a portfolio comprising stocks (Bouri, 2014; Fogarty, 2010; Kourtis et al, 2012; Masset and Henderson, 2010; Masset and Weisskopf, 2010). However, during periods of extreme stress, fine wine was a very weak safe haven against the UK stock market risk.…”
Section: Resultssupporting
confidence: 89%
“…Accordingly, fine wine reduces risk during periods of extreme price movements in UK equities. Our results complement the work of Bouri (2014), who found that wine investment can provide protection against overall downside risk in the stock market.…”
Section: Econometric Analysissupporting
confidence: 89%
See 3 more Smart Citations